2011
DOI: 10.1088/0004-637x/745/1/51
|View full text |Cite
|
Sign up to set email alerts
|

THE EVOLUTION OF PLASMA PARAMETERS ON A CORONAL SOURCE SURFACE AT 2.3RDURING SOLAR MINIMUM

Abstract: We analyze data from the Solar and Heliospheric Observatory to produce global maps of coronal outflow velocities and densities in the regions where the solar wind is undergoing acceleration. The maps use UV and white light coronal data obtained from the Ultraviolet Coronagraph Spectrometer and the Large Angle Spectroscopic Coronagraph, respectively, and a Doppler dimming analysis to determine the mean outflow velocities. The outflow velocities are defined on a sphere at 2.3 R from Sun-center and are organized … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 61 publications
(98 reference statements)
2
12
0
Order By: Relevance
“…The edges of coronal hole boundaries must expand much more rapidly than radially (so-called superradially) in order to fill the space above the streamers. This superradial expansion of field lines at heights of 1-2 solar radii from the surface has been verified observationally with SOHO/UVCS observations (Dobrzycka et al 1999;Strachan et al 2012). Strachan et al (2012) confirm that, for solar minimum conditions, the largest flux tube expansion occurs near the interface of coronal holes and streamers (i.e., the open/closed magnetic field boundaries).…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…The edges of coronal hole boundaries must expand much more rapidly than radially (so-called superradially) in order to fill the space above the streamers. This superradial expansion of field lines at heights of 1-2 solar radii from the surface has been verified observationally with SOHO/UVCS observations (Dobrzycka et al 1999;Strachan et al 2012). Strachan et al (2012) confirm that, for solar minimum conditions, the largest flux tube expansion occurs near the interface of coronal holes and streamers (i.e., the open/closed magnetic field boundaries).…”
Section: Introductionsupporting
confidence: 71%
“…This superradial expansion of field lines at heights of 1-2 solar radii from the surface has been verified observationally with SOHO/UVCS observations (Dobrzycka et al 1999;Strachan et al 2012). Strachan et al (2012) confirm that, for solar minimum conditions, the largest flux tube expansion occurs near the interface of coronal holes and streamers (i.e., the open/closed magnetic field boundaries). Previous modeling efforts of one-and two-dimensional (1D/2D) open flux tubes with prescribed magnetic field geometry and solar wind parameters demonstrated that SAW damping could be a significant contribution to heating in these regions (Jatenco-Pereira & Opher 1989;Narain & Sharma 1998).…”
Section: Introductionsupporting
confidence: 71%
“…The comparison of coronal and heliospheric abundance data support the interpretation that the main contribution to the slow wind comes from the boundary layers of coronal holes, where the outflowing plasma is dynamically fractionated because of the low proton fluxes associated with the large geometrical expansion factors of the flow tubes surrounding coronal streamers. Strachan et al (2012) analyzed the evolution of the outflow velocity and density of the corona, combining the UVCS and LASCO data, in order to measure the expansion of the solar wind from the coronal base to the source surface height, set at 2.3 R , during the transition from the solar minimum of cycle 22 to the rising phase of cycle 23, in the period from 1996 to 1998. When the activity rises and the polar holes shrink, Strachan et al (2012) observe changes not only in the global area of the coronal hole but also in the areal divergence of the flux tubes channeling the solar wind.…”
Section: Elemental Abundances In the Coronal Windmentioning
confidence: 99%
“…Strachan et al (2012) analyzed the evolution of the outflow velocity and density of the corona, combining the UVCS and LASCO data, in order to measure the expansion of the solar wind from the coronal base to the source surface height, set at 2.3 R , during the transition from the solar minimum of cycle 22 to the rising phase of cycle 23, in the period from 1996 to 1998. When the activity rises and the polar holes shrink, Strachan et al (2012) observe changes not only in the global area of the coronal hole but also in the areal divergence of the flux tubes channeling the solar wind. The very large expansion factors of the flux tubes observed near the streamer belt during solar minimum tend to vanish when the overall size of the polar holes decreases.…”
Section: Elemental Abundances In the Coronal Windmentioning
confidence: 99%
See 1 more Smart Citation